2022
DOI: 10.3389/fmed.2022.905085
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relationship of Uric Acid With Fasting Glucose, Insulin, and Insulin Resistance in a United States Cohort of 5,148 Non-diabetic People

Abstract: BackgroundThere is a limited number of studies on the dose-response relationship between serum uric acid and impaired glucose metabolism in people without diabetes, and no large-scale research exploring the relationship in women without diabetes is based on menopausal status. Consequently, the present study aimed to investigate the above relationship in United States adults without diabetes.Materials and MethodsData from 2,498 men and 2,650 women aged ≥20 years were obtained from the National Health and Nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Unfortunately, the study did not analyze women’s true menopausal status. In the United States, results from the National Health and Nutrition Examination Survey [ 17 ] showed that SUA increased the risk of insulin resistance in premenopausal women, but had no effect on postmenopausal women. However, this was a cross-sectional study, and it had certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the study did not analyze women’s true menopausal status. In the United States, results from the National Health and Nutrition Examination Survey [ 17 ] showed that SUA increased the risk of insulin resistance in premenopausal women, but had no effect on postmenopausal women. However, this was a cross-sectional study, and it had certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] Han et al demonstrated a positive correlation between elevated serum uric acid levels and the risk of hyperinsulinemia, as well as a positive correlation between serum uric acid and the risk of insulin resistance (IR) in all individuals except postmenopausal subjects. [ 27 ] In our study, we found a weak positive statistical correlation between uric acid and insulin levels ( R = 0.29; P < .001). A mendelian randomization study indicated that hyperinsulinemia leads to hyperuricemia, but not vice versa.…”
Section: Discussionmentioning
confidence: 43%
“…The meta-analysis ( 18 ) suggested that the OR value of hypertension risk in HUA patients was 1.48, especially in younger patients with early-onset hypertension. Besides, clinical studies ( 19 , 20 ) have found that elevated SUA at baseline can predict the incidence of diabetes and insulin resistance (IR) status, suggesting that elevated SUA is an independent risk factor for IR and diabetes. Our study also found that compared with the NUA group, patients in the HUA group had relatively higher BMI and poorer pancreatic islet and liver function.…”
Section: Discussionmentioning
confidence: 99%